Metabolic regulation of the neural stem cell fate: Unraveling new connections, establishing new concepts - Angelopoulos, Ioannis; Gakis, Georgios; Birmpas, Kyriakos; Kyrousi, Christina; Habeos, Evagelia Eva; Kaplani, Konstantina; Lygerou, Zoi; Habeos, Ioannis; Taraviras, Stavros (Frontiers in Neuroscience, 2022)
The neural stem cell niche is a key regulator participating in the maintenance, regeneration, and repair of the brain. Within the niche neural stem cells (NSC) generate new neurons throughout life, which is important for tissue homeostasis and brain function. NSCs are regulated by intrinsic and extrinsic factors with cellular metabolism being lately recognized as one of the most important ones, with evidence suggesting that it may serve as a common signal integrator to ensure mammalian brain homeostasis. The aim of this review is to summarize recent insights into how metabolism affects NSC fate decisions in adult neural stem cell niches, with occasional referencing of embryonic neural stem cells when it is deemed necessary. Specifically, we will highlight the implication of mitochondria as crucial regulators of NSC fate decisions and the relationship between metabolism and ependymal cells. The link between primary cilia dysfunction in the region of hypothalamus and metabolic diseases will be examined as well. Lastly, the involvement of metabolic pathways in ependymal cell ciliogenesis and physiology regulation will be discussed.